Purinergic Signaling and Aminoglycoside Ototoxicity: The Opposing Roles of P1 (Adenosine) and P2 (ATP) Receptors on Cochlear Hair Cell Survival - Lin, Shelly C. Y.; Thorne, Peter R.; Housley, Gary D.; Vlajkovic, Srdjan M. (Frontiers in Cellular Neuroscience, 2019)
Purinergic signalling regulates important physiological processes and the homeostatic response to stress in the cochlea via extracellular nucleosides (adenosine) and nucleotides (ATP, UTP). Using a previously established organotypic culture model, the current study investigated the effect of purinergic P1 (adenosine) and P2 (ATP) receptor activation on the survival of the sensory hair cell population in the cochlea exposed to the ototoxic aminoglycoside neomycin. Organ of Corti explants were obtained from C57BL/6 mice at postnatal day 3 (P3) and maintained in normal culture medium (with or without purine receptor agonists or analogues) for 19.5 hours prior to neomycin exposure (1 mM, 3 hours) followed by a further incubation for 19.5 hours in culture medium. The cochlear explants were then fixed in 4% paraformaldehyde (PFA) and sensory hair cells labelled with Alexa 488-phalloidin. Neomycin induced a substantial loss of the sensory hair cells, mostly in the middle segment of the cochlea. This neomycin-induced ototoxicity was unaffected by the addition of P2 receptor agonists (ATP and UTP) in the culture medium, whilst the addition of their slowly-hydrolysable analogues (ATPγS, UTPγS) aggravated neomycin-induced sensory hair cell loss. In contrast, the activation of P1 receptors by adenosine or adenosine amine congener (ADAC) conferred partial protection from neomycin ototoxicity. This study demonstrates a pro-survival effect of P1 receptor stimulation, whilst prolonged P2 receptors activation has an opposite effect. Based on these findings, we postulate that P1 and P2 receptors orchestrate differential responses to cochlear injury and that the balance of these receptors is important for maintaining cochlear homeostasis following ototoxic injury. Keywords: Aminoglycoside ototoxicity, Cochlear explant, Sensory hair cells, Adenosine, ATP, P1 receptor, P2 receptor, Purinergic signalling